Revolutionizing Instruction with Flipped Learning: A Workshop for Muhammadiyah High School and Vocational English Teachers in Banyumas Regency - Faisal, Faisal; Anjarani, Shelia; Alim, Condro Nur (Jurnal Pengabdian Masyarakat Bestari, 2024)
Flipped learning is a learning model that moves the delivery of material outside the classroom and focuses understanding inside the classroom with the role of the teacher as a facilitator. This approach increases students' control over learning time and pace, as well as increases participation and critical thinking skills. The integration of Information and Communication Technology (ICT) in English language learning expands access to learning resources and supports collaboration. The challenges of its implementation in high school include teacher readiness and evaluation fit, which can be overcome through training that focuses on the effective application of ICT.